Gone With the Wind, 80 ans d’images. Entretien avec Pierre Berthomieu - Pierre Berthomieu; Emmeline Gros; Marie-Pierre Burquier (Transatlantica)
In an interview with Gaumont’s artistic director Denis Peyrat, a journalist came to the conclusion that “film posters do not obey any miracle recipe.” However, when we consider the many posters of Gone With the Wind or when we talk about the film itself—a film that has survived the years and has never been the object of any remake—we can legitimately wonder if there are not any secret ingredients that would actually account for its longevity. These are some of the questions addressed in this interview with film scholar Pierre Berthomieu (Université de Paris), author of Hollywood, le temps des géants (Pertuis, Rouge profond, coll. “Raccords,” 2009).